MicroRNA-128-3p impaired water maze learning by suppressing Doublecortin expression in both wild type and Aβ-42 infused mice. (28th July 2016) - Chen, Jinlong; Li, Wen; Li, Yuan; He, Songwei; Li, Lingyu; Liang, Lining; Song, Yancheng; Qin, Dajiang; Zheng, Hui
Highlights: miR-128 impaired neural stem cell differentiation by targeting Dcx . miR-128 impaired hippocampal-dependent water maze learning by targeting Dcx . miR-128-DCX axis also functions in mice infused with Aβ-42 Abstract: MicroRNA-128-3p (miR-128) is a brain-enriched microRNA reported to target Doublecortin (Dcx), a key transcriptional factor during adult neurogenesis. However, the downstream physiological effects of this miR-128-DCX axis remain unclear. Here we demonstrated that miR-128 could suppress Dcx expression by complementally binding to the −849 to −856 region of the 3′UTR of mouse Dcx. During differentiation of neural stem cells, over-expressing miR-128 with a lentivirus system inhibited the up-regulation of Dcx on Day 5, subsequently decreasing the percentage of TuJ+ cells on Day 16. Administration of the lentivirus encoding miR-128 into mouse hippocampi significantly impaired water maze learning after 14 days, which could be attenuated when the Dcx-encoding virus was delivered simultaneously. In addition, similar changes including miR-128 up-regulation, Dcx down-regulation and learning defects were observed after a 14-day infusion of Aβ-42, which were also partially reversed by over-expressing Dcx. Collectively, the regulation axis from miR-128 to Dcx is critical for hippocampus-related contextual learning not only in wild type, but also in mice infused with Aβ-42.